2005
DOI: 10.1159/000085290
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Oxysterols and Other Markers of Oxidative Stress, Inflammation and Malnutrition in the Vitamin E and Intima Media Thickness Progression in End-Stage Renal Disease (VIPER) Cohort

Abstract: Background and Objectives: Oxysterols are markers of oxidative stress, levels of which have not yet been reported in hemodialysis (HD) patients. This study was designed to compare levels of the oxysterols 7-ketocholesterol (7KC) and 7β-hydroxycholesterol (7βOH) between a cohort of HD patients and healthy controls. Methods: This nested cross-sectional study reflects baseline (pre-intervention) values for markers of oxidative stress, inflammation and nutrition status in the 160-member vitamin E and carotid intim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…In healthy subjects, oxysterols are found at very low plasma concentrations [210] (Table 1). These concentrations are significantly increased in CKD patients compared to a control population and especially in end-stage renal disease (ESRD) patients undergoing hemodialysis [113,114]. Moreover, Siems et al reported an increase of their concentration after an HD session [114].…”
Section: Oxidized Lipids In Ckd: Evidences Of Toxicitymentioning
confidence: 99%
“…In healthy subjects, oxysterols are found at very low plasma concentrations [210] (Table 1). These concentrations are significantly increased in CKD patients compared to a control population and especially in end-stage renal disease (ESRD) patients undergoing hemodialysis [113,114]. Moreover, Siems et al reported an increase of their concentration after an HD session [114].…”
Section: Oxidized Lipids In Ckd: Evidences Of Toxicitymentioning
confidence: 99%
“…Oxysterols are the derivatives of enzymatic or nonenzymatic cholesterol oxidation, and they may be involved in the initiation and progression of atherosclerosis (7). Many studies have reported the presence of different types of predominantly free radical-induced oxysterols in human lipoproteins, femoral plaques, and atherosclerotic aorta (4,8,9). Conversely, enzymatically generated oxysterols are indicated to play a role in the regulation of cholesterol metabolism (10) and act as important modulators of insulin by acting as agonists of liver X receptors (LXRs) (10).…”
mentioning
confidence: 99%
“…Only seven cross-sectional studies have investigated the possible association between biomarkers of oxidative stress and thickness of the intima-media of the carotid artery. The association was demonstrated in three studies (34)(35)(36), but not in another three (37)(38)(39). In the study by Dursun et al (40), some oxidative stress biomarkers were associated with carotid artery intima-media thickness ( Table 2).…”
Section: Oxidative Stress and Atherosclerosismentioning
confidence: 94%
“…Only seven cross‐sectional studies have investigated the possible association between biomarkers of oxidative stress and thickness of the intima‐media of the carotid artery. The association was demonstrated in three studies , but not in another three . In the study by Dursun et al.…”
Section: Oxidative Stress and Atherosclerosismentioning
confidence: 99%